INSTITUSI PENDIDIKAN PADA MASA DINASTI SALJUQ - Rohana, Syarifah (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2020)
Saljuq Dynasty was founded by Tughril Beg in 429 H/1037 AD. Its government was known as al-Salajiqah al-Kubra (the Great Saljuq or the Glorious Saljuq). The government or Saljuq Dynasty is part of the history of the Abbasiyah Dynasty. It reached its grand leadership and supreme power after they conquered the Buwaihi Dynasti. Their leadership lasted for approximately two centuries. In the era of Saljuq Dynasty there was a rapid rise and awakening of mind pioneered by Nizamul Mulk, the minister of Alb Arislan and Maliksyah. This knowledgeable minister had established a number of schools under his name, Nizamiyah. Those schools were located in many places which include Baghdad, Balkh, Nisabur, Harat, Asfahan, Basrah, Marwu, Amal and Mausil. According to as-Subki, Nizamul Mulk owned a school almost in many cities in Iraq and Khurassan.